Production of solid fuel from oil palm biomass via microwave irradiation pyrolysis technique for co- combustion with coal / Siti Shawalliah Idris - Idris, Siti Shawalliah (Institute of Graduate Studies, UiTM, 2015)
Co-utilisation of coal and biomass deem to be one of the alternatives to reduce climate changes due to global warming. Despite rapid development in this area, no work has been reported on co-firing of coal-biomass char blend derived from oil palm waste. Nevertheless, much research has shown that, lack of synergistic effect was observed during the combustion of the two fuels, resulting in little improvement in combustion efficiency/ emission. Co-firing of coal with biomass char produced from microwave irradiation pyrolysis is undoubtedly a new area and will therefore contribute to new knowledge and novelty in this field. An investigation of co-utilisation empty fruit bunch (EFB), palm mesocarp fibre (PMF) and palm kernel shell (PKS) with subbituminous Mukah Balingian coal and six different blends were carried out via thermogravimetric analyser during pyrolysis and combustion at dynamic conditions in four heating rates. The behaviour of pyrolysis of oil palm biomass using microwave irradiation technique was carried out by exposing the samples at different parameter i.e. power level, exposure time and mass of samples where the best operating conditions was established using Response Surface Method (RSM). Resulting char produced from the optimum conditions were used for the co-combustion characteristics of coal: biomass char blends…